Aspek Hukum Penggunaan Jasa Pihak Ketiga (Debt Collector) oleh Pihak Leasing Berdasarkan Peraturan Otoritas Jasa Keuangan Nomor. 35 Tahun 2018 dalam Upaya Penagihan Kendaraan Roda Dua terhadap Debitur yang Melakukan Wanprestasi - Exshel Benyamin Pou; Sukardan Aloysius; Yossie M. Y. Jacob (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study is to analyze the legal aspects of the use of third party services (debt collectors) by leasing parties based on Financial Services Authority Regulation No. 35/2018 in efforts to collect two-wheeled vehicles against debtors in default. 35/2018 in efforts to collect two-wheeled vehicles against debtors who make defaults The type of research in this study is normative legal research. The research in question is research that has characteristics including gaps in legal norna / principles, does not use hypotheses, uses theoretical foundations / theoretical studies and uses legal materials consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of this study indicate that: (1) The position of debt collectors in the leasing company is as a collection officer not an execution officer, execution can only be carried out by a bailiff with a court decision as in Article 32 of the Fiduciary Guarantee Law paragraph (2). The legal relationship between debt collectors (collection service companies) and creditors, namely debt collectors when carrying out their duties, act based on the power of attorney given by the finance company to the debt collector to collect or collect collateral objects from debtors. Likewise, in POJK No.35/2018 article 50 Financing Companies can cooperate with other parties to carry out collection functions to Debtors. (2) The legal consequences of withdrawing motorized vehicles against debt collectors, debt collectors will be held criminally liable and sentenced to criminal sanctions as stipulated in the Criminal Code as criminal law in Indonesia if the implementation is not in accordance with procedures, as well as the creditor in this case leasing can be sued by the debtor and ask to compensate civilly for the act of withdrawing motorized vehicles by debt collectors if the withdrawal has violated existing provisions and violated the agreement agreed upon by the creditor and the debtor. However, if the implementation is in accordance with the procedure, it must be protected in accordance with applicable laws.